Richard Hofstadter : an intellectual biography - Brown, David S. (David Scott), 1966- (University of Chicago Press, 2006)
Richard Hofstadter (1916-70) was America?s most distinguished historian of the twentieth century. The author of several groundbreaking books, including The American Political Tradition, he was a vigorous champion of the liberal politics that emerged from the New Deal. During his nearly thirty-year career, Hofstadter fought public campaigns against liberalism?s most dynamic opponents, from McCarthy in the 1950s to Barry Goldwater and the Sun Belt conservatives in the 1960s. His opposition to the extreme politics of postwar America?articulated in his books, essays, and public lectures?marked him.